FAKTOR-FAKTORYANG BERHUBUNGAN DENGAN KEJADIAN MALARIA DI DESA KEREKEH KECAMATAN UNTER IWES KABUPATEN SUMBAWA - Aulita Mawaddah; Hamdin Hamdin; Abdul Hamid (Jurnal Kesehatan dan Sains, 2021)
Malaria is an infectious disease caused by the protozoan Plasmodium parasite and transmitted through the bite of the Anopheles mosquito. This study aims to determine the factors associated with the incidence of malaria in Kerekeh Village, Unter Iwes District, Sumbawa Regency in 2021. This research method is a quantitative study with a research design cross sectional. The sample in this study were 85 respondents in Kerekeh Village, Unter Iwes District, Sumbawa Regency. The results of the univariate analysis were obtained from the incidence of Malaria suffering from Malaria as many as 20 respondents (23.0%), good knowledge as many as 25 respondents (28.7%), the work of respondents who worked as many as 46 respondents (52.9%), Habit of using insect repellent 3 respondents (3.4%), Habit of using mosquito nets 37 respondents (42.5%). From the results of thetest, chi square it known is that there is no relationship between knowledge and the incidence of malaria, the value of X2 count (0.177) < X2 table (3.841) or p count (0.647) > p table (0.05), there is no relationship between work and the incidence malaria value X2 count (0.086) < X2 table (3.841) or p count (0.769) > p table (0.05), there is no relationship between the habit of using mosquito repellent with the incidence of malaria value p (0.0548) > p table (0.05), there is a relationship between the habit of using mosquito nets with the incidence of malaria, the value of X2 count (0,11,243) > X2 table (3.841)